Farmers' level of knowledge and perception towards empowerment program in Jambi, Indonesia - Bahtera, Novyandra Ilham (2016)
Among the oil palm supply chain participants, the smallholders are relatively at a disadvantage because of their small farms, low production and other structural problems. An empowerment program is one of the effective measures to improve their economic status. An understanding of perception on empowerment program will help the policy makers to design an effective empowerment program. The study has three objectives which are: to examine the socio-economic profile of oil palm smallholders and their perception and awareness to embrace empowerment program provided by one of the local NGOs named Yayasan Setara Jambi; to examine the association between socio-economic profile of the farmers and their perception towards empowerment program; and to identify the determinants of the oil palm farmers’ participation in training for the empowerment program. Structured questionnaire and face-to-face interview data collection method were employed to obtain the primary data from 194 oil palm smallholders in Tanjung Jabung Barat, Jambi Province, Indonesia. Descriptive analysis is used to profile the respondents and describe their skills and awareness to adopt the empowerment program.Logistic-regression is used to gain information on the determinant of smallholders’ readiness to participate in the empowerment program. The study shows that the majority of smallholders (61.3 %) are about under 45 years old, obtained low level of education, earn income less than Rp 4,300,000 per month, mostly are beginners in oil palm farming and average farm size is 2.75 ha. Majority of the respondents perceive knowledge on Good Agriculture Practices (GAP) as desirable and NGO’s performance as beneficial. However, they give low ratings to the proposition of farmers’ group activities. The level of economic empowerment is still very low. Furthermore, the results of study show that among the socio-economic variables, only monthly income and farming size are significantly related to perception of theirs towards empowerment program. In order to ensure an effective empowerment program, the farmers must achieve a higher level of productivity to enhance income. Logistic regression analysis indicates that knowledge and activities variables have significant effect on the probability of farmers’ participation on the training related with the empowerment program. Income is the major determinant of farmers in involving the training on empowerment program. These results are useful inputs to the government as well as institutions that are responsible in providing empowerment program to the smallholders. ANOVA statistics show that income and farm size variables are positively related with the empowerment program. This indicates that the more monthly income the farmers have and the bigger size of the farm belonging to the farmers, the more they are empowered. It also suggests that the policy maker should focus on improvement of the economic condition of the farmers to enhance their income. Furthermore, the positive relationship between farm size and perception of farmers towards empowerment program suggests the need to institute farmers’ organization such as cooperatives so that small and fragmented farms can be coordinated to achieve a reasonable farm size, hence economies of scale and hence better bargaining power.